The Effect Of Water Quality Based on TSS (Total Suspended Solid), Nitrate (N) and pH Values on The Public Health Degree of Kediri City - Amarin Yudhana; Hariyono; Yuly Peristiowati; Hari Saryono (Universitas STRADA Indonesia, 2026)
Poor water quality can have a significant impact on public health degrees. TSS (Total Suspended Solid), Nitrate (N) and pH parameters are important indicators in determining water quality. This study aims to analyze the effect of water quality based on TSS, Nitrate and pH values on the degree of public health in Kediri City. This study uses an observational quantitative research design with a cross sectional approach. The sample of this study amounted to 100 respondents with a cluster random sampling technique covering 3 sub-districts in Kediri City. The data analysis method uses a linear regression statistical test that looks at the correlation between TSS, Nitrate and pH values on health degrees based on the water quality of the community in Kediri City. Water samples were taken from several river points in Kediri City and analyzed in the PERSADA laboratory. TSS value data is measured using gravimetric method, Nitrate value data is measured using Spectrophotometric, while pH value is measured using pH meter. The results showed that the average TSS value ± 29.6 mg/L (Quality Standard Value according to SNI 6989.3: 2019 is > 50 mg/L), average Nitrate (N) value is 1.24 mg/L (Quality Standard Value according to SNI 6989.79-2011. is 1.6 mg/L) and average pH value ± 7.39 (Quality Standard Value according to SNI 6989.11-2019 is 6-9). For the average value of health degrees based on the water quality of the people of Kediri city, the average ± 30.3 (Max. score of 40). From the results of statistical analysis using linear regression The effect of TSS, Nitrate and pH values on health based on the water quality of the Kediri city community, data were obtained on TSS p value = 0.02, Nitrate p value = 0.876 and pH p value = 0.655 (sig. ≤ 0.05). So it can be concluded that the TSS value has a significant effect on the health status of the people of Kediri city. Meanwhile, the value of Nitrate and pH of water has no effect on the health degree of the people of Kediri city. The results of the study show that the values of TSS, Nitrate and pH of water in the city of Kediri still meet the set Quality Standards. The TSS value has an effect on the public health of the city of Kediri. However, the value of Nitrate and pH of water does not affect the health degree of the community in the city of Kediri. High TSS values, high nitrate values and unstable pH correlate with increased cases of water quality-related diseases, such as diarrhea and skin diseases.